2020
DOI: 10.1242/jeb.227124
|View full text |Cite
|
Sign up to set email alerts
|

Are acute and acclimated thermal effects on metabolic rate modulated by cell size? a comparison between diploid and triploid zebrafish larvae

Abstract: Being composed of small cells may carry energetic costs related to maintaining ionic gradients across cell membranes as well as benefits related to diffusive oxygen uptake. Here we test the hypothesis that these costs and benefits of cell size in ectotherms are temperature dependent. To study the consequences of cell size for whole-organism metabolic rate we compared diploid and triploid zebrafish larvae differing in cell size. A fully factorial design was applied combining three different rearing and test tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 92 publications
3
27
0
Order By: Relevance
“…As predicted, interspecific analyses often show that mass-specific metabolic rate is negatively related to genome size [ 8 , 118 , 205 , 238 , 253 , 256 , 257 , 320 , 325 , 326 , 327 , 328 , 329 ] (but see [ 330 ]). However, intraspecific tests in animals comparing polyploids with diploids have shown that increasing ploidy more often has no effect on metabolic rate than negative effects, and sometimes positive effects have even been observed (reviewed in [ 331 , 332 , 333 , 334 ]; also see [ 335 , 336 ]), as also seen for rates of photosynthesis in plants (e.g., [ 195 , 201 , 293 , 333 ]). Differences in metabolic rate between polypoid and diploid animals may be temperature-dependent [ 334 , 335 , 336 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As predicted, interspecific analyses often show that mass-specific metabolic rate is negatively related to genome size [ 8 , 118 , 205 , 238 , 253 , 256 , 257 , 320 , 325 , 326 , 327 , 328 , 329 ] (but see [ 330 ]). However, intraspecific tests in animals comparing polyploids with diploids have shown that increasing ploidy more often has no effect on metabolic rate than negative effects, and sometimes positive effects have even been observed (reviewed in [ 331 , 332 , 333 , 334 ]; also see [ 335 , 336 ]), as also seen for rates of photosynthesis in plants (e.g., [ 195 , 201 , 293 , 333 ]). Differences in metabolic rate between polypoid and diploid animals may be temperature-dependent [ 334 , 335 , 336 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, intraspecific tests in animals comparing polyploids with diploids have shown that increasing ploidy more often has no effect on metabolic rate than negative effects, and sometimes positive effects have even been observed (reviewed in [ 331 , 332 , 333 , 334 ]; also see [ 335 , 336 ]), as also seen for rates of photosynthesis in plants (e.g., [ 195 , 201 , 293 , 333 ]). Differences in metabolic rate between polypoid and diploid animals may be temperature-dependent [ 334 , 335 , 336 ]. In addition, some studies have shown that, although metabolic rate and its scaling with body mass relate to variation in cell size, they do not relate to variation in genome size [ 337 , 338 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we hypothesize that the cellular architecture of tissue and organs can help ectotherms meet their metabolic demands via the oxygen supply in response to environmental conditions and organismal activity. Following Antoł et al [ 29 ], our study uses a conceptual framework integrating earlier hypotheses about fitness costs and benefits associated with cell size differences among organisms that we refer to as the theory of optimal cell size (TOCS) ([ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; see also a recent review by Kozłowski et al [ 43 ]). According to TOCS, the life history strategies of organisms involve different developmental cellular mechanisms that ultimately decide whether a body consists of many small cells or fewer large cells, which should have vital effects on physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have shown that triploid fish are less able to tolerate environmental conditions that impose physiological challenges on conspecific diploids (e.g., Hyndman et al, 2003; Ojolick et al, 1995; Verhille et al, 2013), which has prevented the wide‐scale adoption of this technology. However, there has been a resurgence of interest in assessing triploid salmonid fishes for use in aquaculture due to improvements in our understanding of their thermal (Riseth et al, 2020; Sambraus et al, 2018; Verhille et al, 2013) and hypoxia tolerance (Benfey & Devlin, 2018; Hansen et al, 2015; Hermaniuk et al, 2021; Sambraus et al, 2017; Scott et al, 2014), and dietary requirements (Sambraus et al, 2020). Despite these advances in understanding the biology of triploid salmonids, they are slow‐growing, cold‐water fish with a long generation time (~3 years) making them a rather impractical model organism.…”
Section: Introductionmentioning
confidence: 99%